The house of the scorpion - Farmer, Nancy 1941- (New York Atheneum Books for Young Readers, 2002)
In a future where humans despise clones, Matt enjoys special status as the young clone of El Patrâon, the 142-year-old leader of a corrupt drug empire nestled between Mexico and the United States
1
Keywords: Cloning -- Fiction; Science fiction